1988
DOI: 10.1002/ajpa.1330760307
|View full text |Cite
|
Sign up to set email alerts
|

Gene frequencies and admixture estimates in the state of Puebla, Mexico

Abstract: Three hundred ninety-three individuals from the Universidad Autónoma de Puebla and its University Hospital were studied to determine the distribution of ABO, MN, Rh-Hr, Duffy, and Diego blood groups; red cell hemoglobin and glucose-6-phosphate dehydrogenase variants; and serum haptoglobins, albumins, and factor Bf types. With the results we estimated that the proportions of black, indian, and white genes are 10.7%, 56.3%, and 33.0%, respectively, in a trihybrid model. Reasons are given as to why the black ance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 13 publications
7
57
2
3
Order By: Relevance
“…On the other hand, differences in allelic frequencies were reported by Kung et al (2010) in different ethnic groups. The findings observed in the study by Kung et al (2010) may be due to genetic background because the Mexican-Mestizo population is comprised of a mixture of Europeans and Africans with native indigenous individuals (Lisker et al 1990). …”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, differences in allelic frequencies were reported by Kung et al (2010) in different ethnic groups. The findings observed in the study by Kung et al (2010) may be due to genetic background because the Mexican-Mestizo population is comprised of a mixture of Europeans and Africans with native indigenous individuals (Lisker et al 1990). …”
Section: Discussionmentioning
confidence: 84%
“…6,11,21,23,[25][26][27][28][29][30] The admixture estimates reported in these studies are based on blood groups, serum proteins, STRs and AIMs. As a whole, the data are consistent with the Mexican population history and reflect a gradient with a higher proportion of Native American ancestry in the southern states and increased ancestry of the African contribution in the states of the Gulf of Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies have shown a proportion of 56% of Amerindian genes, 40% of Caucasian genes and 4% of black genes in this population. [13][14][15] Genetic distances calculated from LMP allele frequencies show that Mexican Mestizos are related to Spaniards and Mexican Amerindians. These data corroborate the previously admixture results reported using other genetic markers and confirm the presence of Spaniard genes (who came to America during the 16th century) in the Mexican Mestizo population.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies have shown a proportion of 56% Amerindian genes, 40% Caucasian genes, and 4% black genes. [13][14][15] The aim of the present work was to study the LMP allele and genotype distribution in Mexican populations and establish the admixture between them and other populations using this polymorphism.…”
Section: Introductionmentioning
confidence: 99%